Squalene/polyethylenimine based non-viral vectors: synthesis and use in systems for sustained gene release. Issue 9 (25th January 2018) - David, Geta; Clima, Lilia; Calin, Manuela; Constantinescu, Cristina Ana; Balan-Porcarasu, Mihaela; Uritu, Cristina Mariana; Simionescu, Bogdan C.
Abstract : New squalene/BPEI conjugates, acting as efficient gene carriers, were included in the 3D matrix, yielding tunable DNA release and long-term bioavailability. Abstract : The design of new non-viral gene vectors and their integration into a biomaterial scaffold are intensively explored nowadays, aimed at developing more efficient gene delivery systems capable of clinical translation. Herein, a series of squalene/branched polyethylenimine (Sq/BPEI) based conjugates were synthesized and their potential in gene delivery, as such or included in a three-dimensional hybrid scaffold (atelocollagen-glycosaminoglycan-polycaprolactone/nano-hydroxyapatite), was investigated. The developed materials were characterized through spectral ( 1 H-NMR, 13 C-NMR, FT-IR) and optical (STEM) techniques. The extent and duration of gene expression for the developed systems were monitored using luciferase assays and fluorescence microscopy. All the investigated systems exhibited a high transfection efficiency without or with moderate cytotoxic side effects (MTS assay data). The best results were obtained with the guanidinylated compound Sq-BPEI-G for both simple and combined polyplex/matrix systems. The polyplex delivery from the hybrid matrix was assessed through kinetic studies using a labeled Sq/BPEI conjugate. For the polyplex (Sq/BPEI – DNA plasmid)/3D matrix system, the expression of the delivered plasmids was observed over a 26 day- period. The reported preliminary data recommend the studied biomaterials as possible candidates for the development of a new gene-activated matrix (GAM) platform.